Physico-chemical and microbiological quality of raw milk produced by smallholder farmers in Gulu City, Northern Uganda - Opiyo, Alfred; Kidega, Kenneth; Okello-Uma, Ipolto; Olum, Solomon (Taylor & Francis, 2024)
Abstract AbstractSmallholder dairy farmers in Northern Uganda sell raw milk to the final consumers without conducting quality control measures. This study evaluated physico-chemical and microbiological quality of milk produced by smallholder farmers in Gulu City. Samples of raw milk were collected from forty (40) smallholder dairy farmers rearing lactating exotic breed of dairy cows (Holstein Friesian) in zero grazing units and eight (8) from milk collection centers. Data were analyzed in SPSS software (version 21.0) by employing descriptive statistics, one-way ANOVA and t-test to separate significant means at 5% level of significance. Significant (P < 0.05) differences were observed in the content of solid-not-fat (SNF), specific gravity, pH value, lactic acid, Coliform count and total plate count of colony forming unit among four divisions in Gulu City. There was no discernible (p > 0.05) difference in protein as well as fat content for milk sampled from the study divisions. In conclusion, smallholder dairy farmers in Gulu City conduct limited recommended key practices for raw milk production leading to compromised microbiological and physico-chemical quality. Further research is needed on in-depth analysis of the different species of micro-organisms in raw milk from both local and exotic breeds of dairy cattle under the smallholder farming system in Northern Uganda.
Keywords: Microbiological quality; physico-chemical quality; raw milk; smallholder dairy farmers